Antibacterial Activity of Selected Essential Oil Components and Their Derivatives: A Review - Vuyolwethu Khwaza; Blessing A. Aderibigbe (Antibiotics)
Essential oils (EOs) are gaining ground and have been intensively studied due to their widespread use in the pharmaceutical, food, and cosmetics industries. The essential components of EOs have been recognized for diverse therapeutic activities and have gained significant attention for their potential antibacterial activities. Despite the popularity of EOs and potent biological properties, their bioactive components and their derivatives are still not comprehensively characterized. This review explores the antibacterial efficacy of selected EO components and their derivatives, focusing on monoterpenes chosen (i.e., carvacrol, menthol, and thymol) and phenylpropanoids (i.e., cinnamaldehyde and eugenol). Furthermore, this review highlights recent advancements in developing derivatives of these EO components, which have shown improved antibacterial activity with reduced toxicity. By summarizing recent studies, this review reveals the potential of these natural compounds and their derivatives as promising candidates for pharmaceuticals, food preservation, and as alternatives to synthetic antibiotics in combating bacterial resistance.